2018
DOI: 10.1080/09593985.2018.1488023
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of individuals with chronic bicipital tendinopathy using dry needling, eccentric-concentric exercise and stretching; a case series

Abstract: Findings from this case series suggest that DN and ECE may be beneficial for the management of patients with chronic LHBT tendinopathy. Further research on the efficacy of this novel treatment approach is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…No signi cant differences were found, this result being striking since previous studies with mechanical loads have suggested that load is a very important factor in tendon response. This fact may be attributed to the speed of execution particularly during the eccentric phase as reported by various authors [53][54][55] and the possibility that these devices may not provide as great an eccentric stimulus as expected and may not dehydrate the tendon as much [56].…”
Section: Resultsmentioning
confidence: 99%
“…No signi cant differences were found, this result being striking since previous studies with mechanical loads have suggested that load is a very important factor in tendon response. This fact may be attributed to the speed of execution particularly during the eccentric phase as reported by various authors [53][54][55] and the possibility that these devices may not provide as great an eccentric stimulus as expected and may not dehydrate the tendon as much [56].…”
Section: Resultsmentioning
confidence: 99%
“…Recent research recommends needling for the treatment of tendinopathy, [41][42][43] but only a single case series specific to dry needling of the LHBT for the treatment of LHBT tendinopathy was identified. 21 A third notable finding was the consensus "disagree" in the theme of biophysical agents on seven of nine items including iontophoresis, phonophoresis, electrical stimulation (interferential current, neuromuscular electrical stimulation and transcutaneous electrical nerve stimulation), ultrasound, and low-level laser (Figure 4). In the theme of other there was also consensus "disagree" on shock wave therapy.…”
Section: Discussionmentioning
confidence: 99%
“…3 As such, the respondents reached consensus on a number of interventions across different themes and subthemes supporting a multimodal approach to treatment. Preliminary evidence on the PT management of LHBT tendinopathy is not robust enough to draw strong conclusions 1,2,13,16,[19][20][21] and few studies focus on a multimodal approach. Therefore, obtaining international expert consensus on a multimodal treatment approach further informs treatment recommendations, which could potentially be utilized prior to electing for surgical options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it follows from the observation of a small group of patients (n = 10) by mcDevitt et al that exercises of an eccentric-concentric character applied in patients with chronic lHbt tendinopathy may be useful in fighting pain, but this requires further observation [106].…”
Section: Lhbt Tendinopathymentioning
confidence: 99%